Association of Soy and Exclusive Breastfeeding With Central Precocious Puberty: A Case-Control Study - Felício, João Soares; de Alcântara, Angélica Leite; Janaú, Luísa Corrêa; de Moraes, Lorena Vilhena; de Oliveira, Maria Clara Neres Iunes; de Lemos, Manuela Nascimento; de Souza Neto, Norberto Jorge Kzan; Neto, João Felício Abrahão; da Silva, Wanderson Maia; de Souza, Ícaro José Araújo; Said, Nivin Mazen; de Lemos, Gabriela Nascimento; et al. (Frontiers in Endocrinology, 2021)
Introduction: While soy is suggested as a possible risk factor, exclusive breastfeeding (EBF) has a likely protective effect in precocious puberty. Our aim was to evaluate the association between both of these variables with central precocious puberty (CPP) Methods: We performed a retrospective, case-control study. A total of 161 girls were divided into two groups: 84 patients diagnosed with CPP composed the case group and 77 patients without the diagnosis of CPP (had gone through normal onset of puberty) were the control group. Results: Our control group had a higher presence of EBF > 6 months, which was an important protective factor for CPP (OR:0.5; IC95%: 0.3-0.9, p=0.05) and also correlated negatively with the presence of it (r = -0.2; p <0.05). Oppositely, the use of soy was significantly higher in the CPP group, (OR: 3.8; IC95%: 1.5-6, p<0.05) and positively correlating (r = 0.2; p < 0.01) with the presence of CPP. Duration of soy intake (years) correlated with bone age (r = 0.415; p <0.05). A logistic regression was performed to evaluate the effects of EBF duration and soy on CPP. The model was significant (x² (2) = 20,715, p = <0.001) and explained 12.2% (Nagelkerke R2) of the variance, correctly classifying 62.5% of cases. EBF was associated with a reduction of likelihood of having CPP (OR = 0,187 (CI = 0.055-0,635); Wald = 7,222, p = 0.007), while soy intake increased the risk (OR = 3.505 (CI) = 1,688-7,279, Wald = 11,319, p = 0.001). Conclusion: Our data found the use of soy was associated with CPP. Additionally, EBF was pointed as a protective factor. However, future prospective studies are needed to clarify this issue.